Tiutiu - Korabov, Nikolai (Bulgaria : SIF, 1962)
Boris Morev, embittered by his miserable existence, is resolved to make it to the top as fast as possible. He leaves his girlfriend Irina and marries the daughter of a wealthy owner of cigarette factory. Profitting from the death of his father-in-law and the mental illness of his wife, he takes over the factory and begins exploiting the workers even more mercilessly. He takes advantage of Irina`s continuing affection and makes her first his mistress and later his wife. Boris plans a big business deal with a Greek tobacco magnate. The deal depends on the approval of the director of the German tobacco concern for Eastern Europe, von Geier. Aware of von Geier's feelings for Irina, Boris asks her to convince him to approve the deal. Irina's love towards Boris slowly turns to hatred as his obsession with money and power grows. As Boris becomes more and more dependent on alcohol, Irina tries to avoid seeing him and spends most of her time with von Geier. Eventually she becomes his lover. Boris hates himself when he sees he has lost the only person he has ever loved. Because of his excessive drinking he develops malaria and dies without completing the business deal he so coveted. Irina buries her husband at the spot they first met.
Keywords: Fiction films